2011
DOI: 10.2522/ptj.20100131
|View full text |Cite
|
Sign up to set email alerts
|

Fear-Avoidance Beliefs Are Associated With Disability in Older American Adults With Low Back Pain

Abstract: Physical activity FABs are independently associated with self-reported disability and overall physical health in older American adults with LBP. High FABs may warrant balance and falls assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 49 publications
5
42
0
1
Order By: Relevance
“…Sions and Higs explained the lack of a significant relation between fear avoidance and disability in their Hispanic patients, which is similar to our results, with the occurrence of fear and avoidance in the context of the severity of pain and external control focus in these patients (32). In the study of Cai et al (5) which they cited, it was stressed that severity of pain partly mediated the relation between fear avoidance behavior and disability.…”
Section: Guclu Dg Et Al: Chronic Low Back Painsupporting
confidence: 80%
“…Sions and Higs explained the lack of a significant relation between fear avoidance and disability in their Hispanic patients, which is similar to our results, with the occurrence of fear and avoidance in the context of the severity of pain and external control focus in these patients (32). In the study of Cai et al (5) which they cited, it was stressed that severity of pain partly mediated the relation between fear avoidance behavior and disability.…”
Section: Guclu Dg Et Al: Chronic Low Back Painsupporting
confidence: 80%
“…Some authors [11,25] have attempted to explain the exact mechanisms and factors related to chronic low back pain, and have reported that a model based on clinical signs and symptoms suggests that intensity and quality of pain are proportional to the extent of tissue injury, which eventually evolves into high levels of disability [27]. However, there is also evidence that the persistence of symptoms of pain cannot be explained by objective clinical findings; therefore, a specific approach based on a biomedical model may prove insufficient due to the complexity of factors that are related to low back pain (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…High ODI scores have been reported to be associated with fear-avoidance behavior, 50 and a moderate correlation between work-related psychosocial factors and physical exposure has been reported 54 ; therefore, these variables were monitored and considered in the analysis.…”
Section: Methodsmentioning
confidence: 99%